A multilevel, multidimensional scale for measuring housing insecurity in urban slums and informal settlements: a psychometric study - Godfred O Boateng, PhD; Ellis Adjei Adams, PhD (Elsevier, 2022)
Background: Housing insecurity is a pervasive challenge in the cities and urban areas of low-income and middle-income countries (LMICs), particularly in the informal settlements where disproportionately high number of urban residents live. Despite this persistent challenge and its impact on health and well-being, there are currently no comprehensive, standardised, and validated instruments for measuring housing insecurity in these regions. We aimed to develop and validate a housing insecurity scale that can be used in urban slums and informal settlements in LMICs. Methods: Using a complementary set of qualitative and quantitative techniques, we used data collected from three urban slums in Ghana (n=1036) on housing deprivations and characteristics, slum severity, resource insecurity, health outcomes, and socio-demography in the development of the scale. Following item generation, domain identification, and content validation, we identified 28 items that were tested for tetrachoric and Biserial correlations. We extracted an optimal number of factors and tested for dimensionality using confirmatory factor analysis and second-order confirmatory factor analysis. We also tested for reliability and validity of the scale. Tests of concurrent and predictive validity were assessed against slum severity scores, and indoor air quality and health status, respectively. Findings: The resultant scale is a multilevel multidimensional scale consisting of 17 items that subdivide into three subscales: lack of essential utility (α=0·63), built environment deficiency (α=0·80), and tenancy challenges (α=0·82). The composite scale was reliable, with a coefficient alpha of 0·83. Concurrent validity showed a significant association between the composite housing insecurity scores and slum severity scores (β=0·29, 95% CI 0·26-0·32). For predictive validity, housing insecurity increased the likelihood of poor indoor air quality (OR 1·35, 1·29-1·42) and poor health (β=0·03, 0·01-0·04). Convergent and discriminant validity and known group comparisons also supported the validity of the scale. Using the mean scores for housing insecurity, about 53·3% of our study population would be classified as experiencing severe housing insecurity in the past year. Interpretation: To our knowledge, this is the first reliable and validated scale developed to measure housing insecurity in urban slums and informal settlements in LMICs. It can be used to test a range of hypotheses about the role of housing insecurity in several environmental and health outcomes; to assess and plan clinical, programmatic, and policy interventions; and to aid in tracking progress made on Sustainable Development Goal 11. Funding: Center for Research and Scholarship Pilot Project Grant (313420) at the University of Texas at Arlington and the Keough School of Global Affairs at the University of Notre Dame.